"A lot of people ignore our culture when it comes to waste management": examining the impacts of culture on solid waste management in two Canadian First Nations. (June 2023) - Assuah, Anderson
Municipal solid waste management approaches in Canadian First Nations have not considered the culture of communities. However, First Nations' way of life is ingrained in their culture. This research examined whether the culture of First Nations impacts municipal solid waste management. A qualitative case study of Peguis First Nation, Manitoba, and Heiltsuk Nation, British Columbia, was conducted, involving 52 semi-structured interviews. Results revealed that avoiding waste, taking care of one another, protecting the land, respecting the land, and connection to the land were cultural factors that influenced participants' municipal solid waste management efforts. Nonetheless, participants indicated that applying these cultural factors to municipal solid waste is not widespread because of culture loss; hence, programs that improve the understanding of culture and highlight the importance of cultural beliefs, values, and teachings in managing waste should be developed. The research concludes that cultural solutions need to be pursued to complement other solutions that aim to improve municipal solid waste management.